1991
DOI: 10.2135/cropsci1991.0011183x003100030059x
|View full text |Cite
|
Sign up to set email alerts
|

Method to Evaluate Ease of Pericarp Removal on Lime‐Cooked Corn Kernels

Abstract: A simple and effective method to evaluate the ease of pericarp removal on lime (CaO)‐cooked corn (Zea mays L.) has been developed. Corn kernels placed in perforated nylon bags are lime‐cooked for 20 min at 98 to 100 °C and then stained in a solution containing methylene blue and eosine Y. We evaluated 11 corn hybrids grown at seven locations in 1989. The relative ease of pericarp removal was affected by hybrid and by growth environment, with hybrid differences being most important. The method requires a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Mean nixtamal moisture content for com in this study was slightly higher than recommended levels, but was very acceptable for distinguishing differences between samples. DML and degree of pericarp removal were similar to other results reported (Serna-Saldivar et al 1991;Sahai et al 2000). Com samples had acceptable nixtamal moisture contents (48-50%), good pericarp removal (>50%), and reasonably low dry matter loss «5%): Syngenta WX7663, Pioneer 33P67, 33R77, 34A31, 3497, 36B08, Horizon 7373, Garst 8383, and Mycogen 2A812.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Mean nixtamal moisture content for com in this study was slightly higher than recommended levels, but was very acceptable for distinguishing differences between samples. DML and degree of pericarp removal were similar to other results reported (Serna-Saldivar et al 1991;Sahai et al 2000). Com samples had acceptable nixtamal moisture contents (48-50%), good pericarp removal (>50%), and reasonably low dry matter loss «5%): Syngenta WX7663, Pioneer 33P67, 33R77, 34A31, 3497, 36B08, Horizon 7373, Garst 8383, and Mycogen 2A812.…”
supporting
confidence: 86%
“…Serna-Saldivar et al (1991) found only a poor negative correlation between pericarp removal and hardness (r = --0.32). Pericarp removal is likely influenced by pericarp properties such as thickness and resistance to alkali steeping that were not measured in this study.…”
Section: Dml and Pericarp Removalmentioning
confidence: 85%
See 2 more Smart Citations
“…Extent of pericarp removal and optimum lime cooking properties were determined according to the nylon bag methods of Serna-Saldivar et al [17,18].…”
Section: Pericarp Removal and Optimum Lime Cookingmentioning
confidence: 99%